Composition distribution and photoluminescence properties of colloidal Cu-doped Zn0.5Cd0.5S quantum dots - Nguyen, Dieu Linh; Nguyen, Thi Minh Hien; Nguyen, Thi Thuy Lieu; Tran, Thi Kim Chi; Nghia, Nguyen Xuan (Vietnam Journal of Science and Technology, 2025)
This study aims to find a solution for preparing Cu-doped colloidal Zn0.5Cd0.5S quantum dots (QDs) with different radial Zn and Cd composition distributions and investigate the effects of these distributions on the QDs’ optical properties. The preparation of QDs with radial gradient composition distribution was performed by quickly and simultaneously injecting Zn and Cd precursor solutions into the reaction flask, whereas QDs with homogeneous composition distribution were prepared by alternately injecting small amounts of the Zn and Cd precursors after preparing crystal nuclei along with thermally annealing the QDs in the reaction solution. Cu doping Zn0.5Cd0.5S QDs decreases their band edge luminescence and significantly increases their broad emission band at lower energy. This emission band is generated by radiative recombination related to the Cu dopant, as well as lattice defects such as interstitial atoms and vacancies. Different composition distributions do not affect the excitation power dependence behavior of band edge luminescence and dopant related emission intensities; however, they cause strong band gap energy renormalizations in Cu-doped ternary QDs with increasing excitation power density. This enhancement is attributed to the optically active region in small gradient alloyed QDs and the existence of a wetting layer surrounding it.